TFB2 is a transient component of the catalytic site of the human mitochondrial RNA polymerase - Sologub, Marina (2009)
Transcription in human mitochondria is carried out by a single-subunit, T7-like RNA polymerase assisted by several auxiliary factors. We demonstrate that an essential initiation factor, TFB2, forms a network of interactions with DNA near the transcription start site and facilitates promoter melting but may not be essential for promoter recognition. Unexpectedly, catalytic autolabeling reveals that TFB2 interacts with the priming substrate, suggesting that TFB2 acts as a transient component of the catalytic site of the initiation complex. Mapping of TFB2 identifies a region of its N-terminal domain that is involved in simultaneous interactions with the priming substrate and the templating (+1) DNA base. Our data indicate that the transcriptional machinery in human mitochondria has evolved into a system that combines features inherited from self-sufficient, T7-like RNA polymerase and those typically found in systems comprising cellular multi-subunit polymerases, and provide insights into the molecular mechanisms of transcription regulation in mitochondria.